A tale of sorcery... - Colfer, Chris, 1990- (Colfer, Chris, 1990- Tale of magic (Series), 2021)
The Southern Kingdom is in the grip of Emperor Seven and his war on both magic, books, and learning; even worse, a malignant darkness is rising and threatening everybody, including Brystal Evergreen, who has gathered allies among the fairies and other magical creatures to confront the threat, but she is also aware that the days of her life are slipping away, and if she does not find the Book of Sorcery in a few weeks she will die.